2018
DOI: 10.1007/s00264-018-3849-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Biomechanical comparisons of current suspensory fixation devices for anterior cruciate ligament reconstruction

Abstract: The original publication of this paper contains mistakes. The first author name "Jin Cheng" is changed to "Cheng Jin ".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Adjustable‐loop femoral cortical suspension devices offer several advantages over fixed‐loop devices [14, 16], however, there are concerns about their tendency to elongate when subjected to biomechanical loading, which may compromise the effective length of the graft‐loop construct [3, 17, 25, 26]. The length of the graft and fixation device construct is critical during the first 8–12 postoperative weeks and early rehabilitation, while the graft heals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjustable‐loop femoral cortical suspension devices offer several advantages over fixed‐loop devices [14, 16], however, there are concerns about their tendency to elongate when subjected to biomechanical loading, which may compromise the effective length of the graft‐loop construct [3, 17, 25, 26]. The length of the graft and fixation device construct is critical during the first 8–12 postoperative weeks and early rehabilitation, while the graft heals.…”
Section: Discussionmentioning
confidence: 99%
“…The more recent cortical suspension adjustable‐loop devices have several advantages: (1) they are easier to use in short femoral tunnels, with placement through the antero‐medial arthroscopic portal; (2) they allow more of the femoral tunnel to be filled with graft, and shorter graft lengths can be used, as seen with tripling/quadrupling of the graft; (3) they are suitable for most tunnel sizes, eliminating the need for fixed‐loop devices with different loop sizes [9, 14, 16, 18]. However, there are concerns about the elongation of cortical suspension adjustable‐loop devices under cyclic loading post‐fixation, which relate to the button‐locking mechanism [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some mechanical studies that compared adjustable-loop devices and fixed-loop devices reported that the latter showed higher breaking strength and less displacement [18][19][20][21][22][23][24][25]. On the other hand, other studies difference in either parameter [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For the other set-ups, the results were close to those obtained in the study of Nye et al [21], reporting values of 682 N for the femur-ToggleLoc™-graft set-up. The pull-out performances of suspended cortical devices reported in the literature are heterogeneous and depend on the implants and protocols studied [1,3,6,9,14,15,21,23,24]. The cortical support of the device seems to enable a greater resistance to ultimate load to failure, although the prestudy could not conirm this hypothesis.…”
Section: Ultimate Load To Failurementioning
confidence: 94%